2020
DOI: 10.1038/s41388-020-1168-9
|View full text |Cite
|
Sign up to set email alerts
|

PIM kinases alter mitochondrial dynamics and chemosensitivity in lung cancer

Abstract: Resistance to chemotherapy represents a major obstacle to the successful treatment of non-small cell lung cancer (NSCLC). The goal of this study was to determine how PIM kinases impact mitochondrial dynamics, ROS production, and response to chemotherapy in lung cancer. Live cell imaging and microscopy were used to determine the effect of PIM loss or inhibition on mitochondrial phenotype and ROS. Inhibition of PIM kinases caused excessive mitochondrial fission and significant upregulation of mitochondrial super… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Recent studies based on immunohistochemical staining found PIM1 to be highly expressed in NSCLC [41,42]. Moreover, increased PIM1 levels were associated with worse prognosis [41] and poorer response to chemotherapy in these tumors [42]. PIM1 was also showed to promote highly aggressive, neuroendocrine variant of prostate cancer by epigenetic changes in H19, suggesting it may be implicated in malignant neuroendocrine transformation [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies based on immunohistochemical staining found PIM1 to be highly expressed in NSCLC [41,42]. Moreover, increased PIM1 levels were associated with worse prognosis [41] and poorer response to chemotherapy in these tumors [42]. PIM1 was also showed to promote highly aggressive, neuroendocrine variant of prostate cancer by epigenetic changes in H19, suggesting it may be implicated in malignant neuroendocrine transformation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies based on immunohistochemical staining found PIM1 to be highly expressed in NSCLC [41,42]. Moreover, increased PIM1 levels were associated with worse prognosis [41] and poorer response to chemotherapy in these tumors [42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that inhibition of PIM kinases causes excessive mitochondrial fission or increased intracellular ROS production and apoptosis. 28 Also, PIM1 knockdown significantly accelerated apoptosis in myoblasts. 29 Therefore, PIM1 may have different roles in different cancer types.…”
Section: Expression Of Genes Associated With the Warburg Effectmentioning
confidence: 96%
“…Consistent results were obtained in the KRas mutant non-small-cell lung cancer (NSCLC), where DRP1 orchestrated a metabolic rewiring to promote lactate utilization and ROS production suppression [ 62 ]. In the same type of tumor, DRP1 was involved in metabolic rearrangements that favored resistance to chemotherapy [ 63 ]. The authors identified a molecular axis represented by Proto-Oncogene Serine/Threonine-Protein Kinase (PIM1), DRP1, and mitochondrial fission; PIM1 inhibition favored DRP1 activity and mitochondrial fragmentation, increasing mitochondrial ROS production and resistance to pharmacological therapy [ 63 ].…”
Section: Fusion and Fission Event In The Onset And Progression Of mentioning
confidence: 99%
“…In the same type of tumor, DRP1 was involved in metabolic rearrangements that favored resistance to chemotherapy [ 63 ]. The authors identified a molecular axis represented by Proto-Oncogene Serine/Threonine-Protein Kinase (PIM1), DRP1, and mitochondrial fission; PIM1 inhibition favored DRP1 activity and mitochondrial fragmentation, increasing mitochondrial ROS production and resistance to pharmacological therapy [ 63 ]. Further studies suggested an antitumoral property of DRP1 in other types of lung cancer.…”
Section: Fusion and Fission Event In The Onset And Progression Of mentioning
confidence: 99%